The Role of Boron Addition on Solidification Behavior and Microstructural Evolution of a High Niobium-Containing TiAl Alloy - Fan Zhang; Zeen Wu; Xiaoye Wang; Tiebang Zhang; Yongchun Zhang; Qiao Li (Crystals, 2023)
This work investigates the role of boron addition in the solidification behavior and microstructural evolution during the heat treatment process of Ti-46Al-8Nb-xB (x = 0.1, 0.7, 1.4, 2.5 at.%). The results show that the solid solution boron element prefers to occupy the interstitial vacancies of the α2 phase in the alloy. However, the solid solubility of the boron element in high Nb-containing TiAl alloys is extremely low. Therefore, it does not have a significant effect on the lattice distortion of α2 and γ phases in the alloy. When the boron content is added up to 0.1%, a B27-type TiB precipitated phase is produced in the alloy. The morphology of borides mostly shows short rod-like structures, and a few show long curved shapes. And the addition of boron refines both the alloy colony size and the lamellar structure. Furthermore, it is also found that boron addition weakens the casting texture of the alloy. After a solid solution and different time aging heat treatment process, the microstructure of different boron content alloys have experienced obvious coarsening phenomenon. However, the morphology of the boride is closely related to boron content and heat treatment.